2012
DOI: 10.2116/analsci.28.65
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction of Protein Crystal Grown in a Nano-liter Scale Droplet in a Microchannel and Evaluation of Its Applicability

Abstract: We describe the technical aspects of the in-situ X-ray diffraction of a protein crystal prepared by a nanodroplet-based crystallization method. We were able to obtain diffraction patterns from a crystal grown in a capillary without any manipulation. Especially in our experimental approach, the crystals that moved to the nanodroplet interface were fixed strongly enough to carry out X-ray diffraction measurements that could be attributed to the high surface tension of the nanodroplet. The crystal was damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…In situ data collection is not new. It has been demonstrated on a number of other crystallization platforms that include vapour-diffusion plates (Bingel-Erlenmeyer et al, 2011;Axford et al, 2012;Cipriani et al, 2012), microfluidic chips (Pinker et al, 2013;Heymann et al, 2014;Perry et al, 2014), acoustically loaded pins (Yin et al, 2014) and microcapillaries (Pineda-Molina et al, 2012), and with nanodroplets (Maeki et al, 2012). However, to date there are but a few examples in which the in situ approach has been implemented with in meso crystallogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In situ data collection is not new. It has been demonstrated on a number of other crystallization platforms that include vapour-diffusion plates (Bingel-Erlenmeyer et al, 2011;Axford et al, 2012;Cipriani et al, 2012), microfluidic chips (Pinker et al, 2013;Heymann et al, 2014;Perry et al, 2014), acoustically loaded pins (Yin et al, 2014) and microcapillaries (Pineda-Molina et al, 2012), and with nanodroplets (Maeki et al, 2012). However, to date there are but a few examples in which the in situ approach has been implemented with in meso crystallogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The microfluidic devices also provide many advantages for X-ray crystal structure analysis, such as allowing on-chip cryoprotection and X-ray diffraction measurement. [26][27][28][29][30][31] Several microfluidic-based platforms, techniques, and approaches for protein crystallization have been studied. Notably, protein crystallization coupled with crystal structure analysis is the most significant methodology for novice researchers involved in protein crystallography.…”
Section: Reviewsmentioning
confidence: 99%
“…We demonstrated in situ X-ray diffraction measurements coupled with droplet-based protein crystallization, and examined the effect of the wall thickness and the material of the capillary used in the X-ray diffraction measurement. 27 Glass and PFA capillaries were used for in situ X-ray analysis. The thicknesses of the capillary walls were 10 and 80 μm for glass and PFA capillaries, respectively.…”
Section: Application For X-ray Analysismentioning
confidence: 99%
“…Recently, several in situ X-ray analysis methods have been reported that improve the efficiency of diffraction data collection and can be applied to membrane protein crystallography studies. [12][13][14] We have also demonstrated the potential for droplet-based microfluidics to obtain a protein single crystal. 15,16 We found that the droplet size was an essential parameter for controlling protein crystallization.…”
Section: Introductionmentioning
confidence: 95%